Tinjauan Yuridis Akibat Perceraian terhadap Pembagian Harta Gono-Gini Menurut Kitab Undang-Undang Hukum Perdata pada Putusan Nomor : 706/Pdt.G/2012/PN.Medan - Binka Lg Simatupang; Taufik Siregar (Jurnal Ilmiah Penegakan Hukum, 2017)
Juridical Review Due to Divorce Against Gono-Gini Property Distribution According to the Civil Code on Decision Number: 706/Pdt.G/2012/PN.MedanThe main goal of humans in slimming is to form a harmonious household. Based on the marriage law number 1 of 1974, marriage is a birth bond between a man and a woman as a husband with a family (household) goal that is pleasant or eternal through the Almighty Godhead. If the divorce occurs indoors, the household can be described as having a result of the person in dispute in the household, where during the marriage, the household that has assets or in everyday language in Indonesia is said to be a "gono-gini" property. In this study, the research engineers are normative juridical, namely research aimed at examining or norms in positive law. The characteristics of this research are analytical descriptive, which is uniquely from the facts to determine something that happened. The purpose of this study was to find out the implementation of the sharing of shared assets and to find out the obstacles to the distribution of shared assets. In addition, in the Compilation of Islamic Law, the distribution of shared assets is also regulated in KHPerdata.